α-Ketoglutarate-related inhibitors of HIF prolyl hydroxylases are substrates of renal organic anion transporters 1 (OAT1) and 4 (OAT4) - Hagos, Yohannes; Schley, Gunnar; Schödel, Johannes; Krick, Wolfgang; Burckhardt, Gerhard; Willam, Carsten; Burckhardt, Birgitta C. (Pflügers Archiv: European Journal of Physiology, 2012)
2-Oxoglutarate or a-ketoglutarate (aKG) is a substrate of HIF prolyl hydroxylases 1-3 that decrease cellular levels of the hypoxia-inducible factor 1a (HIF-1a) in the presence of oxygen. αKG analogs are applied to stabilize HIF-1α even in the presence of oxygen and thus provide a novel therapeutic option in treating kidney diseases. In the kidneys, the organic anion transporters 1 and 3 (OAT1 and OAT3, respectively) in cooperation with the sodium-dependent dicarboxylate transporter 3 (NaDC3) and the OAT4 might be responsible for the uptake of αKG analogs into and the efflux out of the tubular cells. Using the radiolabelled substrates p-aminohippurate (PAH, OAT1), estrone-3-sulfate (ES; OAT3, OAT4), and succinate (NaDC3), N-oxalylglycine (NOG), dimethyloxalyl glycine (DMOG), 2,4-diethylpyridine dicarboxylate (2,4-DPD), and pyridine-2,4-dicarboxylic acid (PDCA) were tested in cisinhibition and trans-stimulation experiments. None of these aKG analogs interacted with NaDC3. 2,4-DPD and PDCA inhibited ES uptake byOAT3moderately. NOG, 2,4-DPD and PDCA, but not DMOG, inhibited PAH uptake by OAT1 significantly. trans-Stimulation experiments and experiments demonstrating stabilization of HIF-1a revealed that NOG and PDCA, but not 2,4-DPD, are translocated by OAT1. All compounds trans-stimulated ES uptake by OAT4, but only PDCA stabilized HIF-1α. The data suggest that OAT1 is involved in the uptake of NOG and PDCA across the basolateral membrane of proximal tubule cells, whereas OAT4 may release these compounds into the primary urine. © The Author(s) 2012.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Hypoxia-Inducible factor; Organic anion transport; Prolyl hydroxylase domains; Proximal tubule